Psychological impacts and self-management by responders to emergency and disaster events involving animals: findings from a cross-sectional international survey - De Grey SJ; Riley CB; Thompson KR; Squance HE; Cogger N (Taylor and Francis Group on behalf of the New Zealand Veterinary Association, 2025)
Aims: To examine the self-reported psychological impacts for professional and volunteer responders associated with attending animal-related emergencies and disasters, focusing on their experience and self-reported management. Methods: An online survey of professional and volunteer responders to animal-related emergencies was shared via social media and international response organisations. Questions addressed demographic, training and event-related factors, perceptions of effects on well-being and post-event management recovery techniques. A particular event was recalled in free-text, and respondents indicated how they had been affected using free-text reflection and Likert scale assessment. The revised Impact of Event Scale (IES-R) was used to identify evidence of possible post-traumatic stress disorder (PTSD). Factors associated with the self-assessed binary outcome of compromised mental well-being (yes or no) were evaluated using single-predictor and multivariable logistic regression. Results: Of 227 responses deemed sufficiently complete for analysis, participants’ rescue experience ranged from 1–60 years; 67% identified as female. Most respondents (57%; 129/227) reported that the incident described affected their mental well-being. A multivariable model found female responders more likely than males to report compromised well-being (OR = 2.37, 95% CI = 1.25–4.57; p = 0.009). The presence of an animal injury (OR = 2.84, 95% CI = 1.44–5.75; p = 0.003), injuries to a member of the public (OR = 3.73, 95% CI = 1.68–8.99; p = 0.002), or a team member (OR = 8.65 95% CI 2.25–57.67; p = 0.006), increased the odds of self-reported adverse mental health outcomes. Six per cent (13/227) of respondents had an IES-R score for which partial PTSD may be a clinical concern, and 3% (7/227) had a score indicative of possible PTSD, including four with a score that has been associated with PTSD and long-term health consequences. Of those who tried well-being support techniques, 95% (187/197) ranked talking with friends, family or teammates as effective. Debriefing with the team or mentor was also effective (95%; 187/197). Socialising was effective for 88% (119/135), and mindfulness or meditation for 87% (91/105). Conclusion and clinical relevance: Responders to emergencies involving animals are at risk of psychological trauma associated with these events, potentially leading to the compromise of mental well-being. Psychosocial supports self-identified as helpful for recovery include talking with others, socialising, physical or recreational activity, debriefing, and mindfulness or meditation, but their effectiveness requires objective evaluation so that education on mitigation and recovery strategies is well-informed.
Keywords: Animals; responder; emergency; disaster; mental health; well-being; post-traumatic stress